Comparison of a new IOL injector system against 3 standard IOL injector systems with different incision sizes: Miyake-Apple view experimental laboratory study. Issue 2 (February 2022) - Zhang, Lu; Schickhardt, Sonja; Fang, Hui; Auerbach, Florian; Cagampang, Perfecto; Merz, Patrick R.; Auffarth, Gerd U.
Abstract : The study compared 1 new IOL injector against 3 standard injectors in porcine eyes. Incision enlargement, ease of use, delivery time and performance were determined. Abstract : Purpose: To compare 1 new intraocular lens (IOL) injector system against 3 standard injector systems in porcine eyes. Setting: David J Apple Center for Vision Research, Department of Ophthalmology, University Hospital Heidelberg, Heidelberg, Germany. Design: In vitro laboratory study. Methods: In 70 porcine eyes, +20.0 diopter IOLs were implanted with the following systems: multiSert, UltraSert, iTec, and RayOne, that is, S1.8 (incision size: 1.8 mm), S2.0 (2.0 mm), S2.2P (2.2 mm, push mode), S2.2S (2.2 mm, screw mode), U2.2 (2.2 mm), iT2.2 (2.2 mm), and R2.0 (2.0 mm). Corneal incision sizes were measured before and after implantation with an incision gauge set. Ease of use was evaluated using a Likert scale. IOL delivery time and performance were determined based on Miyake-Apple view videos. Results: Of the 70 eyes studied, the incision enlargements were 0.36 ± 0.08 mm (S1.8), 0.15 ± 0.07 mm (S2.0), 0.17 ± 0.12 mm (S2.2P), 0.28 ± 0.10 mm (S2.2S), 0.32 ± 0.09 mm (U2.2), 0.30 ± 0.08 mm (iT2.2), and 0.35 ± 0.11 mm (R2.0). Total scores of ease of use were 23.00 (S1.8), 25.00 (S2.0), 29.00 (S2.2P), 26.00 (S2.2S), 26.00 (U2.2), 25.00 (iT2.2), and 24.00 (R2.0). As for the mean delivery time, iT2.2 took the longest time (13.20 ± 3.29 seconds), whereas S2.2S took the shortest time (4.50 ± 0.71 seconds). Optic–haptic adhesion was observed in S1.8 (4, 40%), S2.2P (2, 20%), U2.2 (5, 50%), and iT2.2 (5, 50%). Conclusions: Injector S, with the appropriate incision size and implantation method, could achieve better results regarding incision enlargement, ease of use, delivery time, and performance than other injector systems. There was an indirect relationship between incision size and inadvertent events.